ATTITUDES OF LOAN TAKERS AND CREDIT POLICY OF BANKS IN POST-CRISIS ECONOMY - Elżbieta Rak-Młynarska; Halina Łapińska (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
Last financial crisis caused insolvency of many entities: natural persons, companies, banks and even whole states. The crisis had a serious impact on the real sphere of the economy through channels of financing because the lack of liquidity on the financial market meant stricter credit procedures and more expenisve loans. This, in turn, brought about the fall in the demand for money and cumulation of payment difficulties. It maybe noticed that certain elements of credit policy change along the changing conditions of the economy and situation on the market, influencing the loan takers' behaviour - rise or fall in the demand for loans. The aim of the paper is an attempt to answer the question to what extent the demand for loans is shaped by the attitudes of the entrepreneurs themselves and why not all eceonomic entities are interested in taking out loans despite fulfilling the credit conditions of banks.